Produção de hidromel utilizando graviola (Annonna muricata L.) e feijão-caupi (Vigna unguiculata (L.) Walp.) como suplementos - Sampaio, Kayque Frota (2019)
Honey, the main raw material for the elaboration of mead, is abundant in Brazil, especially in the Northeast region, being rich in fermentable sugars and deficient in many nutrients needed for yeast metabolism in alcoholic fermentation. Therefore, the honey must be added with commercial supplements, fruit in pieces or pulps, spices, among other materials that, in addition to providing nutrients that stimulate yeasts to the consumption of sugars present in the wort, add differentiated sensory characteristics to this beverage. The soursop (Annona muricata L.) is an abundant fruit in the northeastern region of Brazil, with characteristic flavor and aroma, which constitutes a good source of sugars, phenolic compounds and, mainly, fibers. Cowpea (Vigna unguiculata L. Walp) is a leguminous species widely consumed in the north and northeast regions of Brazil, easily found commercially, and has high levels of starch, oligosaccharides and, mainly, proteins. The objective of this work was to obtain a drink through the alcoholic fermentation of honey with soursop supplement and cowpea extract. The commercial strain S. bayanus Premier Cuvée® was selected to the detriment of Cotê des Blancs® (S. bayanus) and Safbrew Abbaye® (S. cerevisiae), for showing lower production of hydrogen sulfide. In fermentations on honey wort supplementation with cowpea extract (0, 5 and 30 g.L-1) higher cell concentration values (1.97 x 108 cel.mL-1), ethanol content (14.1 ± 0.5% v/v) and ethanol volumetric yield (QP) (0.457 ± 0.017 g.L-1.h-1) as well as lower TSS (15.6 ± 0.8 °Brix) and total reducing sugars (59.6 ± 12.6 g.L-1 were obtained with higher extract concentration. The fermentative assays were conducted according to a 23 factorial design with three replications of the central point. The experiments were carried out in Erlenmeyer vials of 500 mL containing 250 ml of half-water and honey (30 ° Brix) under conditions of 30 °C during 288 h to evaluate the effect of pH (3.5, 5.0 and 6.5), soursop concentration (10, 20 and 30% w/v) and percentage of fibrous portion soursop (0, 25 and 50% w/w). Higher consumption values of reducing sugars (90.3%), ethanol (15.5%) and ethanol volumetric yield (0.42 g.L-1.h-1) were obtained in musts with initial pH 5.0, 20% w/v of soursop and mixture of liquid pulp (75% w/w) and fibrous portion (25% w/w). The effect of pH and soursop concentration was significant on the response to fermentative efficiency (εf) after 192 h of fermentation with R² equal to 0.98939. In the results of the central composite planning 2² containing 15 assays, the linear effect of the soursop concentration was significant on QP, with R2 equal to 0.66945. The critical values of soursop concentration (16.55% w/v) and initial pH of fermentation (4.86) at 288 h of fermentation provided the optimum value of volumetric productivity of ethanol (0.410 g.L-1.h-1). In the fermentation of the honey wort in an enlarged laboratory scale, using the previously established critical conditions, a mead containing: maximum cell concentration (7.07 x 107 cel.mL-1) was obtained; Ethanol (14.1%) and QP (0.385 g.L-1.h-1). From the evaluation of the effect of hydrated bentonite, activated charcoal and carboxymethylcellulose (CMC), concentrations equal to 0.5, 1.5 and 2.5 g.L-1, under the clarification of the mead produced on an enlarged laboratory scale, it was found that, at the end of 360 h, the mead was the one with the addition of CMC (1.5 g.L-1), with an increase in transmittance of 10.4 ± 0.5%. It is possible to produce mead using soursop and cowpea extract that can substitute supplements normally used in the production of hydrometer, thus decreasing the costs of the fermentative process and generating a better use of these raw materials